A 260-GHz on-chip cavity-backed slot antenna. Issue 1 (27th July 2018) - Xiao, Jun; Qi, Zihang; Li, Xiuping; Feng, Weiwei; Zhu, Hua
Abstract: This paper presents a cavity-backed dual-slot antenna in 0.13-μm SiGe BiCMOS technology. The dual-slot structure is excited by a cross-shaped strip line and a cavity which is formed by the topmost metal layer connected to the bottom metal layer through vias in between. By adopting dual-slot and cross-shaped feed line, the bandwidth is significantly enhanced by 196% compared with the single-slot antenna with straight feed line. The reason for bandwidth enhancement has been analyzed. The proposed antenna shows a measured impedance bandwidth of 15.2 GHz from 248.2 to 263.4 GHz for | S 11 | < −10 dB. The simulated and measured peak gains of the cavity-backed dual-slot antenna are −1.3 and −2.1 dBi, respectively. The simulated radiation efficiency is 31.1%. The total size of the antenna is 0.46 mm × 0.48 mm.